Assessment of Clinical Outcome of Root Coverage Following Coronally Advanced Flap with or without Amniotic Membrane - M Navarasu; M Umayal; V K Vijay; M Tamilarasan; K Indhu; M S Mugil (Wolters Kluwer Medknow Publications, 2023)
Aim: The present study aimed to assess the clinical outcome of root coverage following coronally advanced flap with or without amniotic membrane in Miller's class I or class II localized gingival recession in relation to anteriors. Methods: Five patients with bilaterally symmetrical Miller's class I or class II localized gingival recession were included in the study. Each patient was divided into control (without amniotic membrane) and test sites (with amniotic membrane) arbitrarily. Clinical parameters including plaque index, probing pocket depth (PPD), clinical attachment level (CAL), and depth and width of the gingival recession were recorded in a pro forma at baseline and in the 2nd, 4th, 12th week. The results were tabulated and subjected to statistical analysis using analysis of variance (ANOVA). Results: A 0.600-mm, 0.400-mm, 2.630-mm, and 2.616-mm reduction in PPD and gain in CAL were observed at control and test sites in the 12th week postoperatively and was found to be statistically insignificant (P = 0.580 and P = 0.871, respectively). Changes in depth and width of the gingival recession were observed and found to be maximum between base line (2.28 mm, 3.01 mm, 2.71, and 3.09 mm) and 2nd week (0.00, 0.00 mm, 0.23, and 0.20 mm) but without statistical significance. Conclusion: From the above results of the study, it could be concluded that the use of amniotic membrane as a barrier along with coronally advanced flap did not influence the clinical outcome of root coverage procedure.